Opportunities and challenges of utilizing well water for aquaculture in Basrah government, Southern Iraq - Ahmed (Iraqi Journal of Aquaculture, 2025)
The current study aimed to assess the environmental and economic feasibility of using well water in fish farming in Basrah Governorate. It reviewed the global importance of aquaculture and its vital role in providing food and income, emphasizing that water quality is a fundamental factor in the success of aquaculture projects. The study discussed the current status of fish farming projects in Basrah and the problems they face due to the deterioration of water quality in the Shatt al-Arab. It also evaluated the possibility of using well water as an alternative, referring to some studies that showed contamination of well water in the governorate. The study relied on the quantitative and spatial distribution of groundwater in Basrah Governorate using satellite imagery processed with Geographic Information System (GIS) software. The current study proposed some modern technologies for treating and purifying well water for reuse in fish farming, with the necessity of establishing environmental, social, and economic controls to ensure sustainability. The study concluded that adopting a comprehensive approach that considers all aspects will contribute to achieving a balance between developmental needs and the preservation of natural resources.